Influence of Children’s Health On Primary School Academic Performance In Uganda. A Case Study of Fort Portal Municipality, Kabarole District, Uganda. - Kanyesige, Brenda (Student's Journal of Health Research Africa, 2021)
Background: The world population comprises 2.2 billion children below 18 years, 1.9 billion of which live in developing countries, 1 billion being caught up below the poverty line, and 340 million in sub-Saharan Africa. 640 million do not have adequate shelter, 400 million do not have safe drinking water and 270 million have no access to health services. In Uganda, better health care is widely thought to improve primary school performance and post-school productivity. This study investigated the influence of children’s health on primary school academic performance in Fort Portal Municipality, Kabarole district. Methodology: Questionnaires were used as the major research tool and it was supplemented through the use of an interview guide and Focus Group Discussion guide. Data collection was then followed by analysis and interpretation of findings. Results: 49.5% of children fall sick at least once a year. 20.6% fall sick once every two months, 15.5% monthly, 8.2% twice a week, and 6.2% once a week. The major effects of poor health on academic performance include; absenteeism, lack of concentration in class, missing tests, and exams. Girls get preferential treatment when it comes to accessing medical care from the school nurse. The study showed that the provision of medicine was viewed as the best option. Conclusion Malaria, cough, and flu are the most common health problem faced by pupils and poor health affects children’s academic performance. Recommendations: Massive sensitization campaign about the spread of cough and flu, enhancing health education in schools, recruitment of nurses that would-be residents in schools, economic empowerment of parents, encouraging more NGOs to the extent their work in health services to Fort Portal Municipality and provide free health services to school-going children as well as regular medical check-up preferably once every three weeks.